Promising markers of CIMP+ colon tumors identified on the basis of TCGA data analysis - G. S. Krasnov; A. D. Beniaminov; R. A. Tychko; G. A. Puzanov; R. O. Novakovskiy; A. V. Kudryavtseva; A. A. Dmitriev (Вавиловский журнал генетики и селекции)
CIMP+ (CpGIsland Methylator Phenotype) tumors are characterized by dense methylation of promoter CpG islands of many genes at once and represent a separate group of malignant neoplasms of the colon. Despite the fact that the diagnostics of CIMP+ tumors has a significant prognostic value, an effective set of markers has not been developed yet. For the identification of CpG sites, the methylation level of which could be used to detect CIMP+ tumors, an analysis of expression and methylation profiles of 297 primary colon tumors and 38 histologically normal tissues paired to them, which are presented in the TCGA (The Cancer Genome Atlas) project database, was performed by us using the CrossHub tool created previously. We developed the scoring, which takes into account the methylation level of CpG sites, their location, and the expression level of the corresponding genes. It was revealed that the methylation status of CpG sites of the AMOTL1, ZNF43, ZNF134, and CHFR genes is a promising marker of CIMP+ tumors. Moreover, specific regions of promoters of these genes, the methylation level of which was associated with the examined phenotype, were identified. To verify the obtained data in independent sampling, first, the quantitative PCR was used to assess the relative mRNA level of the AMOTL1, ZNF43, ZNF134, and CHFR genes in 30 paired (tumor/histologically normal tissue) colon samples. For all the genes, a frequent (50–60 % of cases) and significant (2–30fold) expression decrease was revealed. Then, the bisulfite conversion of DNA followed by cloning and sequencing was applied to examine the methylation status of CpG sites that were selected as the result of bioinformatics analysis. We observed a high methylation level (βvalue = 0.3–0.9) of the CpG sites in the samples with simultaneous downregulation of all 4 genes and a low methylation level (βvalue = 0.0–0.2) in the samples with the unchanged expression level of 4 genes and in histologically normal tissues. Thus, the methylation status of the CpG sites of promoter regions of the AMOTL1, ZNF43, ZNF134, and CHFR genes is a promising potential marker of CIMP+ colon tumors.